Preservation of internal pleurites in a new palaeocorystid crab (Crustacea, Brachyura, Raninoidia) from the Cenomanian (Upper Cretaceous) of Poitou-Charentes, France - Bakel, Barry W. M. Van (Zootaxa, 2013)
A new palaeocorystid crab, Joeranina houssineaui n. sp., is described from upper Cenomanian strata in southwest France. Being apparently derived from J. broderipii, the new species inhabited a sandier substrate environment than its predecessor. The incomplete holotype reveals portions of the internal pleurites, which are rarely seen in extinct crabs.